LOW GENOTOXICITY OF ORGANIC SEA WATER EXTRACTS FROM COVEÑAS (SUCRE, COLOMBIA) - SOLER T., Wilmer; VELÁSQUEZ E., Nelly D.; SOLER A., Juan P. (Vitae, 2009)
Natural sea water is used as a nutritive and therapeutic element in Ibero-American countries, and commercial, refined sea water as a nutritional complement in developed countries. Although treated sea water has no toxicity, as demonstrated by previous sea water ingestion studies, consumption of near-shore seawater poses a health risk due to pollution of nearby urban centers. In this study, human lymphocytes and single cell gel electrophoresis (comet assay) were used to compare the genotoxicity of an organic sea water extract taken near shore with that of sea water samples taken offshore in the small municipality of Coveñas (Sucre, Colombian), where domestic waters are flushed directly into the sea or into septic tanks. Genotoxicity was observed at 37°C, but not at 4°C. This effect depends on the concentration of extract (p<0.0001), the sampling site (p=0.0026), and the interaction of these two factors (p=0.0001). The lowest genotoxicity was observed in offshore organic samples. The cytotoxicity of sea water organic extracts was very low compared to that of the freshwater samples from the water supply system in Medellín (Colombia).